LANDASAN PEMIKIRAN IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001:2008 DI FITK UIN MALANG - Mulyono, Mulyono (J-MPI (Jurnal Manajemen Pendidikan Islam), 2017)
This study aims to examine the foundation of the implementation of ISO 9001: 2008 Quality Management System in improving the quality of learning in the Faculty ofTarbiyah and Teacher Training (FITK) UIN Maulana Malik Ibrahim Malang, the results can be summarized as follows: 1) Making the concept of “Ulul Albab” as a jargon that would be manifested in the form of an educational program under the umbrella of “Ulul Albab”. 2) Realizing a scientific structure that integrates science and Islam with the Treeof Science Metaphor. 3) Trying to anticipate the challenges of higher education both on the national macro and global competition. 4) Realizing organizational health (organization health), to develop academic freedom, innovation, creativity and knowledge sharing. 5) Applying quality assurance consistently. 6) Determined to apply quality culture by implementing QMS ISO 9001: 2008 as international standard quality standard. 7) Implementing the International Quality Management System Organization for Standardization (SSNI ISO) 9001: 2008 to achieve the quality standard of education. 8) Conduct internal audit for continuous improvement of quality (continual improvement). 9) Anticipate various organizational changes at any time and periodic. 10) The ability of leaders to have the vision and confidence to realize his vision. 11) Making the values of the Qur'an (the concept of ihsan: doing better) as the cornerstone of the implementation of the quality management system. 12) Implement the main principles of the quality management system: "Write down what is done and do what is written". 13) Implement a systematic and continuous quality assurance system. 14) The purpose of quality assurance to ensure: compliance, certainty, and relevance. 15) Stipulate the quality points refer to the quality of UIN Maulana Malik Ibrahim Malang. 16) Determined to make quality assurance in academic service.Keywords: Platform, Thought, QMS, Quality, Learning.